The Impact of Hospital Accreditation on Nurses' Perceptions of Quality of Care? - Tejo Trisno; Agit Pratama Putra; Sena W Purwanza (Jurnal Ners, 2019)
Introduction: Accreditation is the recognition of the quality of services that have met the National Hospital Accreditation Standards. In implementing hospital accreditation , it covers patient safety goals, patient-focused service standards, hospital management standards, national programs and integration of health education in hospital services. How is the impact of hospital accreditation on the quality of care, especially nursing services in accordance with the perceptions and attitudes of nurses in hospitals. Therefore, it is necessary to identify the impact of applying hospital accreditation in accordance with nurses' perceptions and attitudes towards nursing services. Methods: For this reason, articles data with a for publication from 2008-2018 are needed, of the 418 systematic literature articles taken from Scopus, Science direct, and Proquest. There are 15 articles chosen to search for literature with keywords; the impact of accreditation on nurses' perceptions and attitudes about the quality of care.Results: Five of the 15 articles that fit the design criteria that address the impact of hospital accreditation according to nurses' perceptions and attitudes in improving nursing services.Conclusion: The study results show that hospital accreditation make a nurses perception the quality of care. Quality of care is the one of impact from hospitals accreditation. Nurses in accredited hospitals feel a higher level of quality of health services.